Visible light-triggered disruption of micelles of an amphiphilic block copolymer with BODIPY at the junction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (Chemical Communications, 2015)
A visible light-cleavable polymer is synthesised to overcome the limitations of UV-sensitive polymers. Photocleavable BODIPY functionalized with an ATRP initiator and alkyne was used to obtain an amphiphilic block copolymer by conducting the click reaction and polymerization simultaneously. Micellar assembly of the polymer was disintegrated under visible light irradiation with controlled release of cargo.

Visible light and pH-responsive star copolymer and doxorubicin-polymer conjugate micelles for combination drug delivery and bioimaging - Basutkar, Nitin B.; Surapaneni, Sai Geetika; Alam, Md. Shafi; Ambade, Ashootosh V. (Journal of macromolecular science part A- pure and applied chemistry, 2024)
Amphiphilic 3-arm star copolymer containing visible light-cleavable BODIPY group and pH-responsive imine bonds at the junction of hydrophilic poly(ethylene glycol) (PEG) and two poly(epsilon-caprolactone) (PCL) arms was synthesized by the combination of ring-opening polymerization (ROP) and click chemistry. The formation and stimuli-responsive disruption of micelles were analyzed using dynamic light scattering and transmission electron microscopy. Dual stimuli-responsive release of anticancer drugs Doxorubicin (Dox) and Camptothecin (CPT) from the micelles was studied. Micellar assemblies containing Dox conjugated to PEG-BODIPY through imine bonds were prepared and controlled release of Dox in response to visible light and pH was shown. CPT and Dox-loaded star copolymer micelles as well as CPT loaded Dox-conjugated micelles were used in cellular uptake studies on MDA-MB 231 cells, and the synergistic effect of the two stimuli on the release of the two drugs was demonstrated inside the cells. Micellar assemblies also showed excellent bioimaging properties in the cellular uptake studies. [GRAPHICS]
Keywords: BODIPY; drug conjugate; micelles; pH-responsive; visible light-responsive